1989
DOI: 10.1152/jappl.1989.67.4.1495
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine's effect on vascular resistance and compliance in the pulmonary circulation

Abstract: Acetylcholine's effect on the distribution of vascular resistance and compliance in the canine pulmonary circulation was determined under control and elevated vascular tone by the arterial, venous, and double occlusion techniques in isolated blood-perfused dog lungs at both constant flow and constant pressure. Large and small blood vessel resistances and compliances were studied in lungs given concentrations of acetylcholine ranging from 2.0 ng/ml to 200 micrograms/ml. The results of this study indicate that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Moreover, Barman and colleagues [1] have suggested recently that a ~table TxA2 analogue, U46619, constricts all pulmonary segments with greater constriction of the small vein in isolated dog lungs. Although a different TxA 2 analogue, STA2, was used in the present study [12], we confirmed the previous suggestion of U46619-induced preferential venoconstriction in dog lungs [1] and reinforced it by the reverse-perfusion procedure. However, the predominance of pulmonary venoconstriction over arterial constriction in response to TxA 2 is not consistent among animal species.…”
Section: Effects Of Sta 2 On Pulmonary Hemodynamics and Lung Weightmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, Barman and colleagues [1] have suggested recently that a ~table TxA2 analogue, U46619, constricts all pulmonary segments with greater constriction of the small vein in isolated dog lungs. Although a different TxA 2 analogue, STA2, was used in the present study [12], we confirmed the previous suggestion of U46619-induced preferential venoconstriction in dog lungs [1] and reinforced it by the reverse-perfusion procedure. However, the predominance of pulmonary venoconstriction over arterial constriction in response to TxA 2 is not consistent among animal species.…”
Section: Effects Of Sta 2 On Pulmonary Hemodynamics and Lung Weightmentioning
confidence: 98%
“…Indeed, pulmonary vasoconstriction induced by arachidonate is ascribed primarily to the cyclooxygenase products, particularly TxA2 [10, 16,18]. Moreover, Barman and colleagues [1] have suggested recently that a ~table TxA2 analogue, U46619, constricts all pulmonary segments with greater constriction of the small vein in isolated dog lungs. Although a different TxA 2 analogue, STA2, was used in the present study [12], we confirmed the previous suggestion of U46619-induced preferential venoconstriction in dog lungs [1] and reinforced it by the reverse-perfusion procedure.…”
Section: Effects Of Sta 2 On Pulmonary Hemodynamics and Lung Weightmentioning
confidence: 99%
“…Previous reports suggest that angiotensin II and U46619 cause modest venous constriction, while bradykinin causes modest relaxation (2,4). It is difficult to predict how such activity would have affected venous particle concentrations or clustering of retained particles, but it emphasizes that pulmonary microvascular perfusion may not be controlled by simple contraction and relaxation of arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…81 Its effects on the pulmonary circulation are likely mediated via the release of NO, and appear to depend on the concentration of acetylcholine administered. 82,83 Lower concentrations of acetylcholine cause vaso-dilation, while higher concentrations appear to cause vasoconstriction. Histamine, a major product released during mast cell degranulation, also has variable effects on pulmonary vascular tone, causing vasoconstriction in some animal models but vasodilation in others.…”
Section: Modulators Of Pulmonary Vascular Tonementioning
confidence: 99%